If i can find a parking spot: A stated choice approach to Grand Teton National Park visitors’ transportation preferences - Newton, J.; Newman, Peter; Taff, B.; Shr, Y.; Monz, C.; D'Antonio, A. (Elsevier BV, 2018)
Managing visitor use in parks and protected areas requires balancing resource protection and quality visitor experiences; a difficult task with ever increasing visitation. Understanding what constitutes a quality experience is also complex. Past studies show that transportation systems are a vital part of visitor's experiences to parks and protected areas. This study investigates preferences for different attributes by examining trade-offs national park visitors make among different transportation-related attributes; such as wait time at the entrance, parking availability, speed of traffic, and volume of traffic. Results indicated that parking was the most important attribute to visitors, followed by traffic volume, wait time at the entrance, and speed. Statistically significant differences in regards to preference among mode of transportation (hiker or in a vehicle) and age were also identified. Management implications: This study investigates the tradeoffs visitors make among different transportation-related experiential attributes along a rustic park road. The findings suggest there are interactions and tradeoffs among different aspects of the transportation experience, such as: • Preference to wait at the entrance station prior to entering the park, rather than in a parking lot waiting for a designated parking space. • Preferences can differ depending on age and mode of transportation.